To Capture A Ring: A Novel Exploring the Effects of Quarter Life Crisis of a Young Adult on Her Relationship - Aurelia Wijaya; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This thesis explores the quarter life crisis (QLC), a common struggle for people in their mid-20s to early 30s who feel stuck and uninspired. Using quarter life crisis theory, it will examine the symptoms, causes, and coping mechanisms to this issue. The research will take the form of a contemporary romance novel, focusing on the main character, Faye. The story follows Faye, who found herself caught between pursuing her dreams and advancing her career, while her mother constantly pressured her to settle down, especially after receiving a wedding invitation from her younger cousin, Maudy. This event intensifies Faye’s internal conflict, making her question her life choices between following her dreams or settling down. Through the story, it can be seen that Faye’s quarter life crisis symptoms are uncertainty feelings, depression and relation concerns. The causes from her QLC are the fear of stepping into a new phase of life, a feeling of disappointment, as well as the potential for more changes ahead. Faye’s coping mechanisms through her QLC are acknowledging the existence of QLC and seeking help.